Tax potential of the North Caucasus Federal District under sanctions: problems, models, institutions of provision - V. V. Roshchupkina (Вестник Северо-Кавказского федерального университета, 2023)
The purpose of the study is to analyze the potential tax opportunities of the North Caucasus Federal District in the conditions of sanctions in force in 2022. The methodological basis was economic and mathematical methods, mathematical modeling. The article describes the percentage of fulfillment of budget assignments for the first quarter of 2022, special attention is paid to the level of arrears in taxes and fees that occur at this time period of the study, the main reasons for its occurrence are characterized. The regions of the district are ranked depending on the level of tax potential in the territory: with a low, medium, high level of tax activity, recommendations are given for its increase in terms of both debt liquidation and reorientation of sub-federal fiscal policy in order to increase tax revenues of the budget system, provide tax preferences to affected sectors of the economy, increase the flexibility of fiscal regulation, shift the priorities of the latter depending on changes in environmental conditions.